2016
DOI: 10.1007/s00382-016-3242-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat and salt redistribution within the Mediterranean Sea in the Med-CORDEX model ensemble

Abstract: Characterizing and understanding the basic functioning of the Mediterranean Sea in terms of heat and salt redistribution within the basin is a crucial issue to predict its evolution. Here we quantify and analyze the heat and salt transfers using a simple box model consisting of four layers in the vertical for each of the two (western and eastern) basins. Namely, we box-average 14 regional simulations of the Med-CORDEX ensemble plus a regional and a global reanalysis, computing for each of them the heat and sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…(2)), and thus only the actual expansion is represented, the interannual variability is similar but a stong positive trend appears (4.48 mm year −1 ). This is due to the warming trend present in LMDZ-MED and already identified by Llasses et al (2016). This trend was driven by the warming of the deepest layers in the Levantine basin and attributed to a too short spin-up, thus being unrealistic.…”
Section: Mediterranean Sea Level Variabilitymentioning
confidence: 90%
“…(2)), and thus only the actual expansion is represented, the interannual variability is similar but a stong positive trend appears (4.48 mm year −1 ). This is due to the warming trend present in LMDZ-MED and already identified by Llasses et al (2016). This trend was driven by the warming of the deepest layers in the Levantine basin and attributed to a too short spin-up, thus being unrealistic.…”
Section: Mediterranean Sea Level Variabilitymentioning
confidence: 90%
“…In summary, in the surface and upper layers, the discrepancies between all the simulations and the reanalyses are in the same range of those obtained in previous works. They are mainly attributed to uncertainties in the surface heat and freshwater fluxes (Nabat et al 2014;Harzallah et al 2018;Llasses et al 2018;Darmaraki et al 2019). In the intermediate and deep layers, the difficulties of the ocean circulation models to reproduce the salinity and temperature trends have also been reported.…”
Section: Present Climate Validationmentioning
confidence: 99%
“…In the intermediate and deep layers, the difficulties of the ocean circulation models to reproduce the salinity and temperature trends have also been reported. Llasses et al (2018) analyzed 14 hindcast simulations from state-of-the-art ocean models and established that present-day regional models can provide reasonable estimates in the surface and upper layers but below 150 m are less reliable. In our case, the trends obtained for AWIs, LMDs, and CNRMs for the temperature and also for ENEA-CNRM-HIST for the salinity are in the range of variability of the state-ofthe-art models for the Mediterranean.…”
Section: Present Climate Validationmentioning
confidence: 99%
“…This study aims at analyzing the dynamics of the Adriatic‐Ionian‐Aegean Sea system using a multimodel approach. The advantages of using a multimodel approach in the Mediterranean region have been shown in the analysis of heat and salt budget (Harzallah et al, ; Llasses et al, ), but also in analysis of atmospheric circulation over the area (Flaounas et al, ). These studies have shown that a multimodel approach is able to describe the main features and mechanisms driving the atmosphere‐ocean circulation over the Mediterranean region (Ruti et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…MedMIT12 (Harzallah et al, ; Llasses et al, ) is the MITgcm (Table , Adcroft et al, ) adapted to the Mediterranean region and implemented at a horizontal resolution of 1/12° with 75 vertical levels. The model covers the whole Mediterranean Sea plus a buffer zone including a small portion of the near Atlantic Ocean.…”
Section: Methodsmentioning
confidence: 99%